Model Pengisian Kepala Daerah Secara Demokratis (Gagasan Terhadap Kegagalan Calon Tunggal dalam Pemilihan Kepala Daerah) - Gunawan Arifin; Imran Imran; Isman Bruaharja (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
This study aims to examine and explain the nature of democratic elections and to formulate a model for democratically filling positions in accordance with the 1945 Constitution of the Republic of Indonesia. This type of research will use normative research with a reflective inventory and evaluation of regulations governing democratic regional head elections, as provided for in the 1945 Constitution of the Republic of Indonesia. Various obstacles to the implementation of elections will be inventoried as input for formulating a democratic position-filling model following the 1945 Constitution of the Republic of Indonesia. The results of the study conclude that: 1) Democratic elections require that the election process uphold democratic values, including the protection of political rights, equality and electoral justice. Regulations governing elections through a single candidate mechanism do not yet reflect democratic elections because they only accommodate the fulfilment of citizens' political rights, namely the right to be elected and to vote, but ignore the values ??of equality and electoral justice; 2). The model for filling regional head positions is based on Pancasila democracy, which requires deliberation to reach consensus grounded in divinity, humanity, unity, and justice.